Handbook of Asian American Health
XVI, 449 p. 3 illus.
Keywords: As a rapidly growing population, America’s Asian community is gaining increased attention from the research and policy sectors. This large, diverse group tends to be viewed as a single entity, yet its subgroups reveal great variety in terms of health, from disease rates and mortality rates to attitudes toward illness and access to care. The Handbook of Asian American Health makes significant inroads toward rectifying this situation by exploring the unique needs and health concerns of particular subgroups within the Asian American community. It consolidates a wide range of knowledge on various health issues impacting Asian Americans while also providing cogent discussion on cultural, social, and structural forces impacting morbidity, mortality and quality of life. Contributors identify key challenges and emerging trends faced by specific ethnic groups regarding diseases and illnesses, describe innovative community-based interventions, and spotlight research areas that need additional study to further advance the understanding of this dynamic population’s complex health concerns. Included in the Handbook: Ethnicity and health: perspectives from nine different Asian-American groups. Social determinants of health: culture, acculturation, socioeconomic status, racism, and more. Critical health/mental health concerns facing Asian Americans, including cancer, cardiovascular disease, diabetes, and Alzheimer’s. Issues in health care delivery: access, quality, and end-of-life care. Social advocacy, health, and the Asian-American community. Complementary and alternative medicine use. The Handbook of Asian American Health breaks new ground for policymakers, social workers, researchers, and academics specializing in Asian-American issues, as well as immigration specialists and health care workers. .